2019
DOI: 10.1017/s0950268819000505
|View full text |Cite
|
Sign up to set email alerts
|

Rates of asymptomatic respiratory virus infection across age groups

Abstract: Respiratory viral infections are a leading cause of disease worldwide. A variety of respiratory viruses produce infections in humans with effects ranging from asymptomatic to life-treathening. Standard surveillance systems typically only target severe infections (ED outpatients, hospitalisations, deaths) and fail to track asymptomatic or mild infections. Here we performed a large-scale community study across multiple age groups to assess the pathogenicity of 18 respiratory viruses. We enrolled 214 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 21 publications
5
57
0
1
Order By: Relevance
“…Among the many pathogens that cause respiratory symptoms, some (like influenza and HMPV) have been shown to be responsible for more severe infections. 4 Our observations here support the hypothesis that the distribution of viral prevalence derived from healthcare-based data is skewed toward more severe pathogens, possibly leading to mis-estimation of the prevalence of infections in the broader population. The findings, validated through scaling using Bayes' theorem, showed that viruses producing more severe symptoms (influenza, HMPV) were overrepresented in the pediatric ED, whereas others, like coronavirus, were substantially underestimated in prevalence.…”
Section: Discussionsupporting
confidence: 80%
“…Among the many pathogens that cause respiratory symptoms, some (like influenza and HMPV) have been shown to be responsible for more severe infections. 4 Our observations here support the hypothesis that the distribution of viral prevalence derived from healthcare-based data is skewed toward more severe pathogens, possibly leading to mis-estimation of the prevalence of infections in the broader population. The findings, validated through scaling using Bayes' theorem, showed that viruses producing more severe symptoms (influenza, HMPV) were overrepresented in the pediatric ED, whereas others, like coronavirus, were substantially underestimated in prevalence.…”
Section: Discussionsupporting
confidence: 80%
“…We refer to both asymptomatic and paucisymptomatic infections as 'subclinical infections'-which are more likely to remain undetected than clinical cases-and refer to the age-specific proportion of infections resulting in clinical symptoms as the 'clinical fraction' . Age-dependent variation in severity has been observed for other respiratory virus infections 17 , including SARS 17,18 . For COVID-19, there are strong indications of age dependence in severity 5,19 and mortality 18,19 among those cases that are reported, which could extend more generally to age-dependent severity and likelihood of clinically reportable symptoms upon infection.…”
mentioning
confidence: 97%
“…Figure 3 shows the total symptom score associated with any 183 coronavirus infection for infections grouped by family cluster. Infection with these viruses generally produces mild and even asymptomatic infection [10]. 194…”
mentioning
confidence: 99%